A fictitious domain decomposition method for the solution of partially axisymmetric acoustic scattering problems. I. Dirichlet boundary conditions - Farhat, Ch; Hetmaniuk, U (International journal for numerical methods in engineering, 2002)
We present a fictitious domain decomposition method for the fast solution of high-frequency acoustic scattering problems characterized by a partially axisymmetric sound-soft scatterer. We apply this method to the solution of various mockup submarine problems, and highlight its computational advantages and intrinsic parallelism.